The Role of the Federal Reserve System During the Great Depression and the Great Recession - Lojkásek, David; Žamberský, Pavel; Jedlinský, Jakub; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The paper compares the policy of the Federal Reserve System during the Great Depression of the 1930s with the Systems policy during the most recent financial crisis known as the Great Recession. The primary goal of the thesis is to find the differences of the policies and steps the Federal Reserve took to moderate the crises and consequently find whether the policies had different outcomes. The first chapter describes the Federal Reserve System, its structure and monetary policy tools. The following chapters 2 and 3 cover the policies of the Federal Reserve during the Great Depression and the Great Recession, respectively. In the conclusion the paper focuses on the outcomes of the two policies and summarizes which of the two was more adequate a response to the respective crisis. The paper should help understand both the role of the Federal Reserve in the U.S. economy and how each of the Systems tools influence the economic environment of the nation.
Vedoucí práce: Pavel Žamberský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses